Kawalan Penyakit Wabak Berjangkit: Satu Tinjauan Terhadap Takaful Mikro Berasaskan Zakat - Hussein 'Azeemi Abdullah Thaidi; Ahmad Zaki Salleh; Muhamad Firdaus Ab Rahman; Irwan Mohd Subri; Azman Ab Rahman (USIM PRESS, 2024)
Vol. 33 No. 3 (2021): ULUM ISLAMIYYAH The Malaysian Journal of Islamic Sciences